60 The correlation between cardiac biomarkers and findings on transthoracic echocardiography in the intensive care unit. A single centre, retrospective study. (16th October 2019) - O' Riordan, F; Carton, M; Coughlan, JJ; Donnolly, M; Fahy, A; Moore, D; Loo, B; Maher, V
Abstract : Background: Trans-thoracic echo (TTE) is a commonly performed non-invasive investigation for the cardiovascular assessment of critically ill patients in the Intensive Care Unit (ICU). Raised cardiac biomarkers are commonly cited as an indication for TTE, however the significance of these biomarker elevations in the critical care setting is unclear. Aim: The aim of this study was to describe findings on TTE in an Irish ICU cohort and to determine if there was any correlation between these findings and serum N-terminal pro b-type natriuretic peptide (NT-proBNP) and high sensitivity troponin T (HsTnT) levels. Methods: We identified all patients admitted to the ICU from January 2018 to February 2019 and a database was formed. We then determined how many of these patients received TTE. Based on TTE findings, patients were divided into two groups: 'Normal TTE' and 'Abnormal TTE'. For the purpose of this study, minor abnormalities including concentric left ventricular hypertrophy, diastolic dysfunction and hyper-dynamic left ventricular function were included in the 'Normal TTE' group. The abnormal TTE group included reductions in LV function, regional wall motion abnormalities and significant valvular heat disease. Continuous variables were expressed as medians and interquartile range. The groups were compared using the z-test for continuous variables and fishers exact test for categorical variables, with a p value of < 0.05 considered significant. Results: There were 358 patients admitted to the ICU during the study period. The mean age was 59.8±17 years and over half of the patients (55%) were male. One hundred and fifteen patients (32%) had a reported transthoracic echocardiogram on our system. Of these echocardiograms, 55% were reported as completely normal and 22% had minor abnormalities. The remaining 23% showed significant abnormalities and were included in the 'Abnormal TTE group'. The prevalence of a NT-proBNP result over 4 times the upper limit of normal (>4xULN) was not significantly different between groups (67% in Normal TTE group vs 71% in Abnormal TTE group, Fisher exact test statistic value: 0.7887, not significant at p<0.05). However a HsTnT value >4xULN was more common in the Abnormal TTE group than the Normal TTE group (73% vs 46%, Fisher exact test statistic value is 0.0231, p<0.05). Similarly, Median NT-proBNP did not differ significantly between the groups; (2254pg/mL; IQR: 11, 758 in the normal group vs 6428pg/mL; IQR: 5, 789 in the abnormal group, p=0.52218) but Median HsTnT level was significantly higher in the abnormal TTE than normal TTE group; (123ng/L; IQR: 656 vs 51ng/L; IQR: 163.5, p=0.0278). Conclusion: TTE is performed commonly in the ICU, with one-third of ICU admissions receiving a TTE in our study. However, over 75% of studies were reported as normal or showing only minor abnormalities. NT-proBNP was commonly significantly elevated in the intensive care setting and this did not correlate with the subsequent diagnostic yield of significant abnormalities on echocardiography. HsTnT levels were more commonly significantly raised in patients with abnormal TTE results and the role of troponin in this setting requires further evaluation.